Calculated XANES Spectra of Cation Off-Centering in Bi(Mg0.5Ti0.5)O3. Issue 1 (2nd January 2016) - Schwertfager, Nuchalee; Pandech, Narasak; Suewattana, Malliga; T-thienprasert, Jiraroj; Limpijumnong, Sukit
Abstract : The x-ray absorption near edge spectra (XANES) of Bi, Mg and Ti in BMT for different off-centering magnitudes, associated with different structural models, were calculated by using first-principles calculations. The models studied include the high symmetric structure, two experimental proposed structures (based on an x-ray diffraction experiment) and the calculated fully relaxed structure (based on the calculated energy optimization). The features in the XANES spectra that relates with the off-center shift of cations were identified. Our calculated XANES will aid future experimental identifications of the detailed structure of BMT.